Visuoperceptual processing in children with neurofibromatosis type 1: True deficit or artefact?. Issue 4 (June 2017) - Van Eylen, Lien; Plasschaert, Ellen; Wagemans, Johan; Boets, Bart; Legius, Eric; Steyaert, Jean; Noens, Ilse
Abstract : Impairments in visuoperceptual processing have long been considered a hallmark deficit of individuals with Neurofibromatosis type 1 (NF1). However, it is unclear which specific visuoperceptual subprocesses are impaired and whether impairments on these tasks really result from visuoperceptual impairments or rather from confounding factors like Executive Functioning (EF) impairments, lower intelligence (IQ) and/or co‐occurring symptoms of Autism Spectrum Disorder (ASD). To answer these questions, we administered four visuoperceptual tasks and two control tasks in 39 children with NF1, 52 typically developing children and 52 children with ASD (8–18 years), all matched for age and gender. Furthermore, EF, IQ, and symptoms of ASD were assessed. Children with NF1 displayed intact visual form discrimination and intact information integration along the dorsal visual pathway. Moreover, their reduced performance on a task requiring integration of information along the ventral visual stream and their more detail‐oriented processing style appeared to result from confounding EF impairments and not from visuoperceptual impairments per se. The co‐occurring ASD symptoms and lower IQ of the children with NF1 did not impact substantially upon their visuoperceptual performance. These findings point to the large impact of EF impairments on the performance of visuoperceptual task and suggest that individuals with NF1 show intact visual form discrimination, intact visual integration, and typical visual processing style when potential confounding factors are controlled for. This may have large repercussions for the interpretation of other findings on visuoperceptual processing in individuals with NF1. © 2017 Wiley Periodicals, Inc.